In vitro activity of norfloxacin, a quinolinecarboxylic acid, compared with that of beta-lactams, aminoglycosides, and trimethoprim. - Neu, H C (1982)
Norfloxacin is a quinolinecarboxylic acid compound. We examined the in vitro activity of this compound against gram-positive and -negative species, including anaerobic species. It inhibited 90% (MIC90) of strains of Escherichia coli at 0.05 microgram/ml, Klebsiella sp. at 0.4 microgram/ml, Salmonella and Shigella spp. at 0.1 microgram/ml, Citrobacter sp. at 0.4 microgram/ml, Enterobacter cloacae at 0.2 microgram/ml, Enterobacter aerogenes at 0.4 microgram/ml, and Enterobacter agglomerans at 0.2 microgram/ml. The MICs of Proteus mirabilis, Morganella sp., Proteus vulgaris, Proteus rettgeri, and Providencia sp. were 0.1, 0.2, 0.8, 0.3, and 1.6 micrograms/ml, respectively. The MIC90 of Serratia sp. was 1.6 micrograms/ml, and that of Acinetobacter sp. was 6.3 micrograms/ml. For Pseudomonas aeruginosa the MIC50, the MIC75, and the MIC90 were 0.8, 1.6, and 3.1 micrograms/ml, respectively. The MIC50 of Pseudomonas maltophilia was 3.1 micrograms/ml, and the MIC90 was 12.5 micrograms/ml. Yersinia, Arizona, and Aeromonas all were inhibited at concentrations below 1 microgram/ml, as was Campylobacter. The activity of the compound against gram-positive species was less impressive: the MIC90s of Staphylococcus aureus, Streptococcus pyogenes, Streptococcus agalactiae, and Streptococcus faecalis were 1.6, 6.3, 3.1, and 12.5 micrograms/ml, respectively. All Listeria strains were inhibited by 3.1 micrograms/ml. The activity of norfloxacine was not affected by the type of medium, pH, or inoculum size. There was no major difference between MIC and minimum bactericidal concentration values. Norfloxacin inhibited bacteria in every species which was resistant to ampicillin, carbenicillin, cephalexin, gentamicin, and trimethoprim at concentrations lower than those of aminothiazolyl cephalosporins, moxalactam, and aminoglycosides.